Chapter Il futuro dell'Europa - Fiolhais, Carlos (Libere carte, 2023)
One of David Sassoli's most outstanding initiatives was the Conference on the Future of Europe, concluded in 2022, which aimed to promote the European construction based on the voices of citizens. Given the Europe's historical relevance in the development of science and technology and my own European experience, I comment on this Sassoli's "political testament", highlighting three major challenges for Europe and arguing that, in addition to science and technology, the future of the European Union must be based on the values ​​he espoused.